Collaboration between Halal Companions and MSMEs: Maximizing Social Media for Halal Product Promotion - Romi Mesra; Asep Rahman (PT. NALURI EDUKASI PRESS, 2024)
This study aims to analyze the collaboration between halal assistants of the Ministry of Religious Affairs and MSMEs in maximizing the use of social media for halal product promotion. Using a qualitative approach with a systematic literature review, this study explores the challenges, effective strategies, and impacts of the collaboration. The results of the study indicate that this collaboration has the potential to increase the effectiveness of digital promotion of MSME halal products through the synergy between halal technical knowledge and digital marketing skills. Key findings include the importance of educational content, the role of online communities, the effectiveness of influencer marketing, and the need for continuous capacity development. Analysis using various digital communication theories and other relevant theories reveals the complexity and potential of this collaboration in increasing the competitiveness of MSME halal products in the digital era. Research implications include recommendations for policies and programs that support systematic collaboration between halal assistants and MSMEs in the context of digital promotion.